Prince Fly Guy - Arnold, Tedd (Arnold, Tedd. Fly Guy, 2015)
Buzz is writing a fairy tale for homework, and Fly Guy naturally assumes the role of a handsome prince, who fends off a giant and rescues a beautiful princess.